A Tripartite Zero Knowledge Authentication Protocol based on Elliptic Curve Weil Pairing - Roy, Parthajit (International Journal of Computer Sciences and Engineering, 2025)
Secret sharing is an important cryptographic protocol having many striking applications in reality. In a fraudulent model, it is even more difficult to compute because, fraud will also know the secrets and will impersonate as a valid secret share holder thereafter. This paper proposes a model for zero knowledge identification of authentic secret shareholders based on Elliptic curves. The model considers Chinese remainder theorem based secret sharing scheme for oblivious computations. The proposed model uses Weil pairing based tripartite Diffie-Hellman model on Elliptic curves and the model only says whether the participating parties are true shareholders or not without reviling any secret information. The paper also discusses the computational aspects the proposed models and possible weaknesses of the model.